Do Histologically Aggressive Subtypes of Papillary Thyroid Microcarcinoma have Worse Clinical Outcome than Non-Aggressive Papillary Thyroid Microcarcinoma Subtypes? A Multicenter Cohort Study - Zuhur, Sayid Shafi; Aggul, Hunkar; Avci, Ugur; Erol, Selvinaz; Tuna, Mazhar Muslum; Uysal, Serhat; Altuntas, Yuksel (Georg Thieme Verlag Kg, 2023)
Histologically aggressive micropapillary thyroid carcinomas (PTMC) subtypes are thought to be associated with an aggressive clinical course. However, evidence for unfavorable clinical outcomes in patients with aggressive PTMC subtypes is not clear. In this study, we intended to determine the difference in clinical outcomes between patients with aggressive and non-aggressive PTMC subtypes. In this multicenter cohort study, the computer-recorded clinical and histopathological data of patients who underwent thyroid surgery between January 2000 - January 2021 in 9 referral centers and were diagnosed as PTMC were analyzed. A total of 1585 patients [female 1340 (84.5%), male 245 (15.5%), mean age 47.9 +/- 11.63 years), with a mean follow-up time of 66.55 +/- 37.16 months], were included in the study. Ninety-eight cases were diagnosed as aggressive and 1487 as non-aggressive subtypes. Persistent/recurrent disease was observed in 33 (33.7% )and 41 (2.8%) patients with aggressive and non-aggressive subtypes (p < 0.001). Diseases-free survival rates were markedly lower in patients with aggressive than in those with non-aggressive PTMC subtypes (66.3 vs. 94.8%, log-rank p < 0.001). Moreover, in multivariate analysis, aggressive histology was an independent predictor of persistent/recurrent disease, after controlling for other contributing factors (HR 5.78, 95% CI 3.32-10, p < 0.001). Patients with aggressive PTMC subtypes had higher rates of incomplete biochemical and structural response than patients with non-aggressive subtypes as well (p < 0.001). Aggressive PTMC subtypes share many characteristics with histologically identical tumors > 1 cm in size. Therefore, the histopathological subtype of PTMC should be taken into consideration to tailor a personalized management plan.
Keywords: papillary microcarcinoma; aggressive subtype; clinical outcome